Pengembangan Sistem Informasi Pelayanan Ibu Hamil Pada Platform Android Berbasis Lokasi (Studi Kasus: Puskesmas Karangploso Kabupaten Malang) - Muhammad Hafidz Rahman; Herman Tolle; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
During the period of 2013 to 2015, the mortality rate of pregnant women and infants in Malang Regency is still high. Based on data obtained from the Health Office of Malang Regency, 2013 until 2015 on average as many as 125 babies and 15 pregnant women die every year. PUSKESMAS as one of the health worker has done its best to help reduce AKI(Maternal Mortality Rate) in Malang Regency. But in the process of implementation, PUSKESMAS often encounter obstacles in the data collection of pregnant women. In fact, data collection is still using manual method so that it can cause difficulties in data collection and checking. In addition, if there is an emergency condition which requires the PUSKESMAS to take action, it is often encountered an obstacle in finding the patient's address because of poorly recorded rural road conditions. Whereas at that time it takes time and action as effectively as possible to avoid events that can be fatal to the safety of mother and child. Solutions that can be used by PUSKESMAS by utilizing technology in doing data collection to pregnant mother that is by making information system that can record pregnant woman who do control. PUSKESMAS midwife can also do data collection of pregnant women using location based service technology, making it easier for PUSKESMAS to find the location of the patient's house.